(untitled) (The Research of Medical Science Review, 2025)
Background: One of the riskiest operations is open-heart surgery, which involves a sternotomy (thoracic opening) in which the patient's chest is opened using a surgical instrument to access the patient's heart. The desired operation to correct the underlying disease or abnormality is carried out by the surgeon under direct visualization. Since the heart is the body's most vital organ and performs the vital life-sustaining function of pumping blood throughout the body, its care is also crucial. For this reason, patients are kept in a cardiac intensive care unit following surgery in order to closely monitor both the patients' and the heart's health. The length of stay in the cardiac critical care unit affects both the patient's and the heart's health. The length of time spent in the cardiac critical care unit is dependent on a few perioperative variables that can be managed and assessed prior to the procedure for improved results. Method: Using a non-probability convenient sampling technique, 247 patients who had on- pump open-heart surgeries and were admitted to the cardiac intensive care unit were included in this cross-sectional descriptive study design. Group 1 consisted of patients who were in the CICU for less than 48 hours, whereas Group 2 included patients who stayed in the CICU for more than 48 hours. Between the two groups, a number of perioperative risk variables were compared. Results: 81% of the patients were in Group 1 (less than 48 hours in the intensive care unit), and 19% were in Group 2 (more than 48 hours in the intensive care unit). Risk factors that were found to have a significant impact on length of stay in the cardiac critical care unit included postoperative blood transfusion, re-intubation, re-operation, aortic cross-clamp time (minutes), intubation time (≥24 hours), and LVEF percentage. Conclusion: Our findings suggest that preoperative left ventricular ejection fraction (LVEF), intraoperative cross-clamp time, and postoperative complications such as blood transfusion, re-intubation, and re-operation significantly contribute to prolonged CICU stays. While demographic factors such as age, gender, and body mass index (BMI) did not show a significant association with extended CICU stay, the presence of intraoperative and postoperative complications played a pivotal role. These results emphasize the need for proactive patient management strategies to optimize cardiac function preoperatively, minimize intraoperative complications, and enhance postoperative recovery. Implementing targeted interventions to address these risk factors could significantly reduce CICU stay durations, improving patient outcomes and optimizing resource utilization in healthcare settings.